ANALYSIS OF SEMANTIC DENSITY IN LEGAL DOCUMENTS - Indah Arti Fisilla; Wawan Gunawan (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
This study investigates how context and complexity are often realized in legal documents. The area of investigation covers a thought of complexity representing knowledge practice in the legal discourse. This study used qualitative inquiry involving linguistic analysis and description. The data were taken from six written legal documents including three decrees and three police summons published in the internet in 2019-2020. The analysis shows that legal documents are featured with linguistic characteristics in realizing knowledge to maintain and change social relations, increase consciousness of readers, representing their own discourses. The practical implications of this analysis are discussed in this paper esspecially to interpret readability of the legal texts for common readers.